2021
DOI: 10.1242/bio.054635
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila model of anti-retroviral therapy induced peripheral neuropathy and nociceptive hypersensitivity

Abstract: The success of antiretroviral therapy (ART) has improved the survival of HIV-infected patients significantly. However, significant numbers of patients on ART whose HIV disease is well controlled show peripheral sensory neuropathy (PSN), suggesting that ART may cause PSN. Although the nucleoside reverse transcriptase inhibitors (NRTIs), one of the vital components of ART, are thought to contribute to PSN, the mechanisms underlying the PSN induced by NRTIs are unclear. In this study, we developed a Drosophila mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…While highly effective at controlling HIV infection, anti-retroviral therapy (ART) is also associated with the development of peripheral sensory neuropathy (PSN) in select patients [ 150 ]. Bush et al demonstrated how ART with AZT (Zidovudine or Azidothymidine) can induce thermal and mechanosensory nociceptive hypersensitivity in larvae [ 218 ]. This sensitization was associated with degeneration in sensory neurons, as measured by an increase in fragmented terminal (distal) dendrites in C4da neurons.…”
Section: Neuroinfection and Neuroimmunity Models In Drosophilamentioning
confidence: 99%
“…While highly effective at controlling HIV infection, anti-retroviral therapy (ART) is also associated with the development of peripheral sensory neuropathy (PSN) in select patients [ 150 ]. Bush et al demonstrated how ART with AZT (Zidovudine or Azidothymidine) can induce thermal and mechanosensory nociceptive hypersensitivity in larvae [ 218 ]. This sensitization was associated with degeneration in sensory neurons, as measured by an increase in fragmented terminal (distal) dendrites in C4da neurons.…”
Section: Neuroinfection and Neuroimmunity Models In Drosophilamentioning
confidence: 99%